STRENGTHENING LEADERSHIP MANAGEMENTS AS A SOLUTION TO ISLAMIC EDUCATION PROBLEMS - Sastri Dwi Kurnia Nasution (JELIM : Journal of Education, Language, Social and Management, 2023)
This study describes the strengthening of educational leadership as a solution to the problems of Islamic education. The approach in this study was carried out with a descriptive qualitative approach. Data collection was obtained using observation, interviews, and documentation studies. Data analysis in this study used data reduction techniques, data presentation, and concluding/verification. Checking or checking the validity of the data used credibility, transferability, dependability, and confirmability techniques. The results of this study indicate that strengthening educational leadership is the most important and urgent variable to create/realize quality Islamic education. As a leader who should be followed and can be used as an ideal model for leadership, namely: Sidiq, Amanah, Tablig, and Fathonah. Strengthening educational leadership is a balance between the concepts in leadership solutions in Islam and Islamic principles and placing the task of leadership not only as a responsible humanitarian task but also answering the problematics of Islamic education. Strengthening educational leadership and developing the quality of Islamic educational institutions will be greatly influenced by the leadership developed by individuals in leading Islamic educational institutions.